Effect of the density and of the distance of Brachiaria decumbens Staff on the initial growth of Coffea arabica L. seedligns - Marcolini, Livia Weyand; Alves, Pedro Luís da Costa Aguiar; Dias, Tomás Carneiro de Souza; Parreira, Mariana Casari (Coffee Science - ISSN 1984-3909)
The aim of this work was to evaluate the interference of three densities (4, 8 and 16 plants/m2) of Brachiaria decumbens Stapf distributed at three different distances (0, 10 and 20 cm from coffee plants) on the initial growth of Coffea arabica L. seedlings. Dark red Latosoil was used as substrate to fill up 70 liters cement boxes. Coffee seedlings at 15 cm height and 8 leaves stage were planted in each box. B. decumbens seedlings were transplanted when they reached two to four leaves stage. The experimental design was a randomized blocks with ten treatments and three replications. At the end of the experiment were measured, height, leaf number, leaf area, chlorophyll content and dry weight of coffee plants. Dry weight of B. decumbens leaves was also evaluated. The leaf area and leaf dry weight was shown to be more sensitive parameters to the interference of Brachiaria plants. Dry weight of coffee plants were reduced from 60% to 88% when the B. decumbens were transplanted 0 cm from the coffee plant. With distance of 10 cm the reduction of dry weight increased with the increase of the density of the B. decumbens. In the coexistence of the coffee plants with 16 plants/m2 of B. decumbens, there was a reduction in the dry weight of about 80% at the distances of 0 and 20 cm. Regarding leaf area, the reduction was 47% on the average in the density of 4 plants/m2 of B. decumbens The reduction in leaf area at other densities was higher at the distance of 0 and 20 cm, and 55% reduction was obtained at the distance of 10 cm.